PERGESERAN TRADISI PEMBUATAN JALUR PADA MASYARAKAT KABUPATEN KUANTAN SINGINGI - Rapni Yelti; Isjoni Isjoni; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: In making the pathway, it turns out that there are also elements of Malay culture, namely pantun. Pantun is not only used in a variety of social activities, but also in the pathway culture. The Pantun is the most widely known form of Malay literature. In the past pantun was used to complete daily conversation. Even now most Malay people in the countryside still use it. Starting from the background of the problem, the writer can formulate the problem, namely "What is the meaning of pantun in making the path for the people of Kuantan Singingi Regency?" The place of research is the people of Kuantan Singingi Regency. When this research was conducted for 6 months from the research proposal, the seminar continued with thesis writing up to the bachelor's exam. In this study researchers used structured interviews. This means that researchers have made a list of questions to be submitted to research respondents. Based on the presentation and analysis of the data, it can be concluded that the results of this study are: 1) the values contained in the pathway in Kuantan Singingi Regency include: family values, courtesy values, artistic values, religious values, hard work values (enthusiasm and trying), the value of cooperation and the value of sportsmanship. 2) the meaning of pantun in boat building is the path that is made if not with Allah's permission as good as any form it will not be able to speed and good because all the paths will not be the same, wood assisted must follow its shape. 3) the Rapat Banjar tradition in boat building. 4) choose the three in boat building. 5) the tradirion of manobang in boat building. 6) the carpenther tradition in boat building. 7) the tradition in maelo jalur of boat building.Keywords: Tradition exchange, track runway